APLIKASI PRINSIP GOOD CORPORATE GOVERNANCE DALAM PENGELOLAAN BADAN USAHA MILIK DESA KENCANA MUKTI DESA PURO KECAMATAN KARANGMALANG KABUPATEN SRAGEN - SARI, ANA NOVITA (Journal of Politic and Government Studies, 2020)
Kencana Mukti village-owned enterprise of Puro Village, Karangmalang, Sragen established on December 2016 which now has 3 business units, namely the village financial institution, The Puro Market, and Puro mart in order to enhance the welfare of the society of Puro village. In managing the Kencana Mukti village-owned enterprise, good corporate governance that has 5 principles namely transparency, accountability, responsibility, independence, and equity. The problems of this study are how is the application of good corporate governance in the management of Kencana Mukti village-owned enterprise of Puro village, Karangmalang, Sragen and what is the obstacle that occurs in Kencana Mukti villageowned enterprise. This study uses descriptive qualitative method. This study is conducted in Kencana Mukti village-owned enterprise, Puro, Karangmalang, Sragen. This study uses qualitative data collection method through in-depth interview and documentation. . In this study, the primary data is obtained directly from the informant who is considered to know best of the problem of this study through in-depth interview. The secondary data is obtained from the documents belong to Kencana Mukti village-owned enterprise such as articles of association, financial reports, journals, village profile, village-owned enterprise profile, and law and regulation. The result of this study shows that the application of good corporate governance in managing Kencana Mukti village-owned enterprise has failed. It is caused by the administrators have not worked professionally that obstruct the running of Kencana Mukti village-owned enterprise. It resulted in the stagnation of one of the business units, Puro Mart. The other obstacles that occur are the inability of Kencana Mukti village-owned enterprise to pay the employee fully, the location is not strategic, and lack of human resources. Therefore, it is expected that the village government provides training to the employee of village-owned enterprise about the good management and leadership and rearrange the business plan and business target of Kencana Mukti village-owned enterprise